Analysis of Water Suitability for Ecotourism Development on Several Beaches in Morella Village, Central Maluku Regency, Maluku Province - Leiwakabessy, Fredy; Kubangun, Muhammad Tarmizi; Pattiasina, Eifan Boyke (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2025)
Maluku is an archipelago whose territory is coastal and marine which is suitable for tourism. The tourism value and attractiveness of coastal areas should be developed through marine tourism. This study aims to analyze current speed, water depth, pH, DO, temperature, salinity, sigma-t, chlorophyll-a, and turbidity-m as physical, chemical, and biological indicators in the Lubang Buaya and Moki Beach ecotourism areas. Water sampling was carried out using Kemmerer bottles at different depths, namely at the surface and at a depth of 20 meters.Water samples are used to analyze chemical elements both horizontally and vertically. Sample analysis was carried out at the Oceanology Laboratory and Basic Biology Laboratory of Pattimura University.The test parameters in this study were water depth, temperature, salinity, sigma-t, chlorophyll-a, turbidity-m using conductivity, temperature, and depth (CTD), current speed using a current meter, pH using a pH meter, and dissolved oxygen (DO) using a DO meter. The waters of Lubang Buaya Beach and Moki Beach, Morella Village, Central Maluku Regency, Maluku Province have water conditions, namely pH, temperature, salinity, sigma-t, chlorophyll-a, turbidity-m, and brightness with appropriate categories, while DO with an inappropriate category based on water assessment standards. The assessment results show the waters' suitability for ecotourism development at a surface depth of 0 meters and a bottom depth of 3 to 25 meters. The minimum current speed of 0.003 m/s and the maximum current speed of 0.36 m/s are suitable for boating, banana boating and jet skiing activities.